Pengaruh Variasi Orientasi Serat pada Komposit Hibrida Rami/E-Glass terhadap Kekuatan Tarik dan Kekuatan Bending - Nurul Islam Muhammad Irfa; Firmansyah Hendrix Noviyanto; Permata Shafira Nur (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2025)
Hybrid natural–synthetic fiber composites have gained increasing attention as lightweight and sustainable materials for structural applications. This study investigated the mechanical properties of hybrid composites reinforced with natural ramie fiber and synthetic E-glass fiber as potential materials for helmets that comply with the Indonesian National Standard (SNI) requirements. The composites were fabricated using the hand lay-up method with different fiber volume fraction ratios: A (20% ramie: 10% E-glass), B (10% ramie: 20% E-glass), C (15% ramie: 15% E-glass), and D (25% ramie: 5% E-glass), while maintaining a constant total fiber content of 30% and 70% epoxy matrix. Prior to fabrication, the ramie fibers were treated with a 5% NaOH alkali solution to enhance the fiber–matrix interfacial bonding. Mechanical characterization was conducted through tensile and flexural tests based on the ASTM D638 and ASTM D790 standards, respectively. The results showed that Specimen B exhibited the highest tensile strength and elastic modulus, reaching 104.38 MPa and 5063.02 MPa, respectively. Meanwhile, the highest flexural strength was obtained for Specimen A, with a value of 41.11 MPa and a flexural modulus of 635.89 MPa. All composite configurations satisfied the minimum strength requirement for SNI-standard helmets (33.93 MPa). However, several defects, such as voids, fiber pull-out, and delamination, were observed, which were mainly attributed to incomplete resin infiltration during the hand lay-up process. Therefore, the application of vacuum bagging or other assisted molding techniques is recommended for future studies to reduce internal defects and improve the quality of composites